2018
DOI: 10.1093/schbul/sby027
|View full text |Cite
|
Sign up to set email alerts
|

Hyper- and Hypomentalizing in Patients with First-Episode Schizophrenia: fMRI and Behavioral Studies

Abstract: Mentalizing deficits in FES consists of hypo- and hypermentalizing. The neural pattern of FES patients is consistent with deficits in the ability to switch off mentalizing processes in potentially social contexts, instead increasing them when intentionality is not forthcoming. Overall, results demonstrate complexities of theory of mind deficits in schizophrenia that should be considered when offering social cognitive training programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
33
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 59 publications
(84 reference statements)
3
33
0
3
Order By: Relevance
“…We hypothesized that individuals with glossolalia show hypermentalization in the absence of mental illness, depressiveanxious features, or enhanced schizotypal traits. In contrast, patients with schizophrenia are characterized by both hypo-and hypermentalization, together with a decreased accuracy in the description of the ATT animations (Bliksted et al, 2016(Bliksted et al, , 2019. We also hypothesized that hypermentalization is related to the subjective experience of intrinsic religiosity.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…We hypothesized that individuals with glossolalia show hypermentalization in the absence of mental illness, depressiveanxious features, or enhanced schizotypal traits. In contrast, patients with schizophrenia are characterized by both hypo-and hypermentalization, together with a decreased accuracy in the description of the ATT animations (Bliksted et al, 2016(Bliksted et al, , 2019. We also hypothesized that hypermentalization is related to the subjective experience of intrinsic religiosity.…”
Section: Introductionmentioning
confidence: 96%
“…Concerning the psychopathological model of glossolalia, it is notable that altered mentalization is a well-replicated feature of schizophrenia (Abu-Akel and Bailey, 2000;Frith, 2004;Brune, 2005;Bora and Pantelis, 2013;Bliksted et al, 2016Bliksted et al, , 2019Martinez et al, 2019). Some patients exhibit a weakened attribution of mental states (hypomentalization), resulting in social isolation and inflexible communication, which is reminiscent of that seen in individuals with autism-spectrum disorders (Martinez et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While Das et al found reduced activation of the right superior temporal gyrus (STG), the temporo-parietal junction (TPJ) and bilateral inferior frontal gyri (IFG) (Das et al, 2012a;2012b), Martin et al showed increased activation of bilateral IFG, left STG and left caudate nucleus (Martin et al, 2016). Finally, Bliksted et al found that patients hyper-mentalized during non-social stimuli, accompanied by increased activation of the anterior medial prefrontal cortex (Bliksted et al, 2018).…”
Section: Introductionmentioning
confidence: 99%